2010
DOI: 10.1093/carcin/bgq114
|View full text |Cite
|
Sign up to set email alerts
|

Functional and physical interaction between the selenium-binding protein 1 (SBP1) and the glutathione peroxidase 1 selenoprotein

Abstract: Selenium-binding protein (SBP) 1 is present in reduced levels in several cancer types as compared with normal tissues, and lower levels are associated with poor clinical prognosis. Another selenium-containing protein, glutathione peroxidase 1 (GPX1), has been associated with cancer risk and development. The interaction between these representatives of different classes of selenoproteins was investigated. Increasing SBP1 levels in either human colorectal or breast cancer cells by transfection of an expression c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 44 publications
5
95
0
Order By: Relevance
“…Numerous experimental studies had suggested that the intestinal epithelial cell as a model of intestinal metabolism had been successfully used for trace elements. [27][28][29][30] In the present study, the primary cultured intestinal epithelial cells of the crucian carp, Carassius auratus gibelio, were used to evaluate the effect of nano-Se with different sizes and concentrations on related enzyme activities and protein contents.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experimental studies had suggested that the intestinal epithelial cell as a model of intestinal metabolism had been successfully used for trace elements. [27][28][29][30] In the present study, the primary cultured intestinal epithelial cells of the crucian carp, Carassius auratus gibelio, were used to evaluate the effect of nano-Se with different sizes and concentrations on related enzyme activities and protein contents.…”
Section: Discussionmentioning
confidence: 99%
“…Examples in M. galloprovincialis include thioredoxin peroxidase (also known as peroxiredoxin), which detoxifies hydrogen peroxide or organic peroxides (Cox et al, 2010), and carbonyl reductase, which metabolizes lipid peroxidation products like carbonyl-containing aldehydes (Ellis, 2007). The function of selenium binding protein-1 is not known, but it may interact with glutathione peroxidase and thus affect the scavenging of ROS indirectly (Fang et al, 2010). In M. trossulus, DyP-type peroxidase catalyzes the conversion of H 2 O 2 into H 2 O (Sugano, 2009).…”
Section: Cold Acclimationmentioning
confidence: 99%
“…Sample values obtained with specific primer sets were normalized to β-actin primer set values. For qRT-PCR, the following primer were used: β-actin, forward, 5'-GTCCACCGCAAATGCTTCTA-3' and reverse, 5'-TGCTGTCACCTTCACCGTTC-3'; GPx-1, forward, 5'-CC AAGCTCATCACCTGGTCT-3' and reverse primer, 5'-TCGAT GTCAATGGTCTGGAA-3' as recently described by us (20).…”
Section: Real-time Reverse Transcription-pcr (Rt-pcr) Analysismentioning
confidence: 99%